Genomic surveillance of antimicrobial resistance shows cattle and poultry are a moderate source of multi-drug resistant non-typhoidal Salmonella in Mexico. - Enrique Jesús Delgado-Suárez; Tania Palós-Guitérrez; Francisco Alejandro Ruíz-López; Cindy Fabiola Hernández Pérez; Nayarit Emérita Ballesteros-Nova; Orbelín Soberanis-Ramos; Rubén Danilo Méndez-Medina; Marc W Allard; María Salud Rubio-Lozano (PLoS ONE)
Multi-drug resistant (MDR) non-typhoidal Salmonella (NTS) is a public health concern globally. This study reports the phenotypic and genotypic antimicrobial resistance (AMR) profiles of NTS isolates from bovine lymph nodes (n = 48) and ground beef (n = 29). Furthermore, we compared genotypic AMR data of our isolates with those of publicly available NTS genomes from Mexico (n = 2400). The probability of finding MDR isolates was higher in ground beef than in lymph nodes:χ2 = 12.0, P = 0.0005. The most common resistant phenotypes involved tetracycline (40.3%), carbenicillin (26.0%), amoxicillin-clavulanic acid (20.8%), chloramphenicol (19.5%) and trimethoprim-sulfamethoxazole (16.9%), while more than 55% of the isolates showed decreased susceptibility to ciprofloxacin and 26% were MDR. Conversely, resistance to cephalosporins and carbapenems was infrequent (0-9%). MDR phenotypes were strongly associated with NTS serovar (χ2 = 24.5, P<0.0001), with Typhimurium accounting for 40% of MDR strains. Most of these (9/10), carried Salmonella genomic island 1, which harbors a class-1 integron with multiple AMR genes (aadA2, blaCARB-2, floR, sul1, tetG) that confer a penta-resistant phenotype. MDR phenotypes were also associated with mutations in the ramR gene (χ2 = 17.7, P<0.0001). Among public NTS isolates from Mexico, those from cattle and poultry had the highest proportion of MDR genotypes. Our results suggest that attaining significant improvements in AMR meat safety requires the identification and removal (or treatment) of product harboring MDR NTS, instead of screening for Salmonella spp. or for isolates showing resistance to individual antibiotics. In that sense, massive integration of whole genome sequencing (WGS) technologies in AMR surveillance provides the shortest path to accomplish these goals.